Gaming as a potential source of conflict with real life: The youth’s assessments - A. K. Mamedov; G. V. Denissova; O. V. Smirnova; O. V. Sapunova (RUDN journal of Sociology)
Today, gaming practices seem to be at the forefront of the formation of a future society. In the current era of global digital transformations, the moment of total public involvement in the new digital reality was recorded in 2016, when an augmented digital reality was widely introduced and adopted. Thus, the period of post-post-modernity started with the situation, in which a person is at a loss facing an elusive old world with new features rather than a “brave new world”. However, some grounds for forecasting future trends have been accumulated, which allows the authors to argue that behind the most striking manifestations of digitalization affecting social reality, there is the totality of their influence on many aspects of everyday life. The hidden restructuring of social practices that comes with every new multiplayer game is determined by both the gameplay of players involved and business structures that use psychological and digital tactical and strategic achievements for their own commercial purposes. The total gamification of social practices will become a new “bottleneck” for the contemporary civilization, if we do not manage to integrate a humanitarian approach and humanistic expertise into the strategic control centers for the development of digital technologies. The article presents the results of the survey conducted to reveal the general tendency in the youth’s attitude towards the key aspects of life under the increasing digitalization (socializing, communication and learning) and to find out whether gaming might positively contribute to them or, on the contrary, should be considered a potential threat. The results of the survey show that the youth define both offline and online communication as equally important parts of their life and tend to restrain from total gamification but only in the field of education. The danger of getting addicted seems to be the most notable disadvantage of gaming, although in general it is viewed rather as an entertaining pastime provided the ability to keep it under control.